2014
DOI: 10.1177/1071100714549188
|View full text |Cite
|
Sign up to set email alerts
|

The Sensitivity of Standard Radiographic Foot Measures to Misalignment

Abstract: If a researcher or clinician is interested in measuring the CPA or TNCA, the current best practices guidelines for obtaining ML and AP images should be closely followed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 15 publications
(38 reference statements)
0
15
0
Order By: Relevance
“…A general limitation of BA measurement is the risk of measurement errors due to interobserver variability or inability to correctly align the foot in standard radiographs; this misalignment can lead to errors in measurements [25,28]. Interobserver variability in BA was classified as moderate [26] or good regarding agreement between independent observers [29].…”
Section: Discussionmentioning
confidence: 99%
“…A general limitation of BA measurement is the risk of measurement errors due to interobserver variability or inability to correctly align the foot in standard radiographs; this misalignment can lead to errors in measurements [25,28]. Interobserver variability in BA was classified as moderate [26] or good regarding agreement between independent observers [29].…”
Section: Discussionmentioning
confidence: 99%
“…However, a clinical observation at the radiology departments in multiple centers in the Netherlands showed that the posture of the patient was highly variable when radiographing the foot according to the already mentioned criteria. This could be a possible explanation for the discrepancy between clinical findings and the appearance on X-ray, which was also mentioned in the literature [16,23]. Therefore, the purpose of the present study was to evaluate the effect of standing posture on the osseous relationships of the foot.…”
Section: Introductionmentioning
confidence: 78%
“…The first important aspect for an adequate radiograph is the position of the center of the X-ray beam, as well as the angle of the X-ray beam in relation to the foot [15,16]. Several studies demonstrated that standardizing these procedures, give reproducible results for radiographic foot measurements [9,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…However, the reason why this letter is written is that, if we define accuracy as closeness of the measurements to a specific true value, caution must be recommended in defining “accurate” those measurements taken on 2-dimensional images (bidimensional fluoroscopic or radiographic images), which by definition and especially in the foot and ankle field are biased by the superimposition of bones and by the rotation of the x-ray source or of the foot. 1,8 As a consequence, the assessment of the intra- and interobserver reliability along with a power analysis to verify whether the lack of statistical significance in the difference between the Captain’s view and the actual angulation is dependent on a type II error (ie, false negative) would be recommendable before adopting this new measurement in clinical practice. In the future, the diffusion of the already existing intraoperative 3-dimensional imaging (such as the 3D fluoroscopy 3,4 or the C-arm CT 2 ) will likely help overcome the limitations inherently related to radiographs, enabling one to obtain truly accurate calculations based on a volume and not on single plane measurements.…”
mentioning
confidence: 99%